Bed load transport from a regenerated forest catchment in Sarawak - Gerusu, Geoffery James (Faculty of Civil Engineering, UTM, 2005)
This note presents preliminary results of a study on bed load transport from a 0.6 km2 forested catchment in Sarawak, Malaysia, once affected by logging activities. The influence of rainfall and stream discharge on bedload production was investigated. The estimated 6 months total bedload of the study area was 0.54 tons or 0.18 t/ lcm2/month.